Application of Flow Pattern Map for Solving Liquid Loading Problems in Well AA - Steven Chandra; Wijoyo Niti Daton; Johannes Marcel Susilo (Penerbitan Universitas Trisakti, 2022)
About two-thirds of fields that exist in the world right now are classified as mature fields. Mature fields usually have a lot of problems that occurred during production. Mature field is classified as field which has produced as much as fifty percent of their established proved plus probable resources estimation or has produced for more than twenty-five years. Empowerment of mature well can be increasing the efficiency of well productivity. Productivity decline can be caused by low maintenance of flow pattern in a well. The other problems which commonly happen is decreasing of reservoir pressure of the well, liquid loading, slugging, and high water cut percentage. Several methods can be used to solve a lot of problems in mature well. The methods can be applied to get an optimum well productivity result. This study shows that Well AA has a slug flow pattern using matching method on a flow pattern diagram. Gas injection and velocity string are applied to solve the problems for Well AA. Gas rate of about 12 MMSCFD is obtained with gas injection method to get annular flow pattern and three different sizes of velocity string are used which are 1.25 inch, 1.5 inch, and 2.0625 inch with churn flow pattern. It is identified that the use of velocity string of 1.25 inch is the optimum method for Well AA.